The relationship between Gram Sabha and Gram Panchayat - John, M.S.; Chathukulam, Jos (1999)
A workable relationship between Gram Sabha and Gram Panchayat is yet to crystalize in most of the states in India. However, to hasten the process of vesting Gram Sabha with greater powers would only entail conflicts between Panchayat and Gram Sabha, leading to weakening of the process of decentralisation. An effective Gram Sabha is possible only with the willing cooperation of the representatives of the people after the Panchayat has been invested with sufficient powers. - Reproduced
Keywords: Panchayat - India; Rural development - India; Panchayat